Munasabah Al-Quran: Studi Menemukan Tema Yang Saling Berkorelasi Dalam Konteks Pendidikan Islam - Rahmat Sholihin (Fakultas Syariah UIN Antasari, 2018)
ABSTRACTThe Holy Qur'an was revealed by Allah as a guide for Italian people, especially for those who are devout. Understanding the instructions contained in the Al-Quran needs to be supported with related sciences, for example: asbab an-nuzul, munasabah, makki and madani and so on. The study of the chronological historicity of the verse is seen from asbab an-nuzul science. Not all verses of the Koran have specific asbab nuzul, to complete it, the science of munasabah is offered as an effort to correlate between verses (surah) in the Koran.The source of knowledge from this munasabah is based on ijtihadi, so there are differences about the various variations. This paper will discuss the relationship between themes and sub themes in the educational approach. This research results that in the theme of education using the term apperception, which is connecting between the lessons that are issued with the lessons to be discussed by connecting various related themes. so that the theme of the verse will always be related to the same scientific pattern until the discussion is finished. ABSTRAKKitab suci Al-Quran diturunkan Allah swt sebagai petunjuk buat manusia Italia, terkhusus lagi bagi orang yang bertaqwa. Memahami petunjuk yang terkandung dalam Al-Quran perlu disupport dengan ilmu-ilmu yang terkait, misalnya: asbab an-nuzul, munasabah, makki dan madani dan seterusnya.Studi tentang historisitas kronologis turunya ayat dilihat dari ilmu asbab an-nuzul. Tidak semua ayat Al-Quran memiliki asbab nuzul yang spesifik, untuk melengkapinya ditawarkan ilmu munasabah sebagai upaya untuk mengkorelasikan antar ayat (surah) dalam Al-Quran.Sumber ilmu dari munasabah ini didasarkan pada ijtihadi, sehingga terdapat perbedaan tentang berbagai ragamnya. Tulisan ini akan membahas tentang hubungan tema dan sub tema dalam pendekatan pendidikan. penelitian ini menghasilkan bahwa dalam tema pendidikan menggunakan istilah apersepsi, yaitu menghubungkan antara pelajaran yang dikeluarkan dengan pelajaran yang akan dibahas dengan menghubungkan berbagai tema yang terkait. sehingga tema ayat akan selalu berhubungan dengan pola keilmuan yang sama hingga selesai pembahasannya.